The Social Impact of Michael Jackson’s ‘Heal the World’ on Youth Awareness - Alia Afifa; Jamaluddin Nasution; Citra Intan Christine Gea; Angel Herlin Chintya Harefa; Grace Asni Natalie Hulu; Mutiara Pia Gratia Situmorang (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the representation of humanistic values in Michael Jackson's song